Synergistic cryoprotective effects of mannan oligosaccharides and curdlan on the grass carp surimi - Yanxin Lin; Lingzhi Zhang; Wanting Tang; Jing Ren; Yijie Mo; Xiao Guo; Lizhong Lin; Yuqin Ding (Food Chemistry: X)
The cryoprotective effects of mannan oligosaccharides (MOS) and curdlan (CU) on the quality of grass carp surimi after freeze-thaw cycles (FTCs) were assessed using the response surface methodology. The optimal contents of MOS (6.79 %, w/w) and CU (0.45 %, w/w) produced minimum thawing losses and the highest gel strength of surimi after five times FTCs. MOS, CU, and their mixture demonstrated cryoprotective effects on grass carp surimi. Compared to MOS or CU alone, MOS-CU displayed synergistic cryoprotective effects, as evidenced by the better prevention of thawing losses of surimi, the superior retardation of the aggregation and denaturation of MP, the amelioration of the gel strength and WHC of surimi gel. Moreover, the MOS-CU mixture demonstrated cryoprotective effects equivalent to those of commercial cryoprotectant on grass carp surimi from zero to five times FTCs and even outperformed CC after seven times FTCs.